Unchecked : the untold story behind Congress's botched impeachments of Donald Trump - Bade, Rachael; Demirjian, Karoun (William Morrow, an imprint of HarperCollins Publishers, 2022)
Washington Post journalists Rachael Bade and Karoun Demirjian write about the inner workings of President Trump's impeachment.